A comparison of quadriceps-to-hamstrings ratios during isokinetic testing, cutting, and drop landings in male soccer players - O'Donnell, S.; Eitan, D.; Roper, J. L. (International Journal of Exercise Science, 2020)
Collegiate soccer is not an unusual place to suffer a knee injury. The sport has many dynamic movements, such as cutting, jumping and shooting. Many professionals use quadriceps-to-hamstring (Q/H) ratios as a tool to determine when an injured player can to return to game play or use the ratio to investigate how predisposed a certain player is to sustaining a knee injury. However, many of these ratios are taken in isokinetic testing in a controlled environment and to our knowledge it is unknown if these ratios are similar to those measured during dynamic activity. Therefore, this study investigated if there was a relationship between Q/H ratios measured during isokinetic testing and drop landings and cutting. Fifteen Division 2 collegiate male soccer players (age: 19.79 ± 1.25 years; height: 176.74 ± 6.22 cm; weight: 77.24 ± 11.01 kg). Wearing Athlos© compression shorts participants performed isokinetic testing, drop landings and cutting drills while muscle activity was measured. A significant difference was found between the bilateral Q/H ratios during the drop landings (p= 0.04; h= 0.49). There were no significant bilateral differences measured during the cutting drills in either direction and isokinetic testing (p> 0.05). Additionally, there was so significant relationship in Q/H ratios between isokinetic testing and the dynamic movements (p > 0.05). This suggests that clinicians should use Q/H ratios during dynamic movements rather than isokinetic testing in a controlled environment to better assess player risk disposition and return-to-play criteria.